2006
DOI: 10.1111/j.1741-3729.2007.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

In the Context of Risk: Supportive Adults and the School Engagement of Middle School Students*

Abstract: Many students in the United States, particularly those from lower income or racially/ethnically diverse families, are exposed to clusters of risk factors that have a negative impact on school success. This study examined the association between the number of supportive and caring adults in the home, school, and neighborhood and the school engagement of students in early adolescence. Results revealed that students who reported such supportive adults in their lives also reported higher levels of psychological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
141
2
15

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(167 citation statements)
references
References 49 publications
9
141
2
15
Order By: Relevance
“…Academic engagement, as in the present study, is conceptualised as the extent to which students are psychologically and behaviourally engaged in academic tasks (Appleton et al 2006;Van de Grift 2007). Students who have positive perceptions about teacher support show good behavioural engagement with schooling and obtain high learning achievements (Woolley and Bowen 2007). Additionally, student engagement in classroom activities serves as a starting point for good academic grades (Finn 1989).…”
Section: Teaching Behaviour and Student Engagementmentioning
confidence: 99%
“…Academic engagement, as in the present study, is conceptualised as the extent to which students are psychologically and behaviourally engaged in academic tasks (Appleton et al 2006;Van de Grift 2007). Students who have positive perceptions about teacher support show good behavioural engagement with schooling and obtain high learning achievements (Woolley and Bowen 2007). Additionally, student engagement in classroom activities serves as a starting point for good academic grades (Finn 1989).…”
Section: Teaching Behaviour and Student Engagementmentioning
confidence: 99%
“…Engagement with high school is often described in terms of the behaviours that students engage in which involve them in school activities (Wooley & Bowen, 2007). The influence of involvement in school extracurricular activities has been demonstrated to influence the rate at which school students drop out (Mahoney & Cairns, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was not surprising as previous research has recognized that schools serving low-income, minority, and immigrant students tend to be at a disadvantage for academic success (Crosnoe, 2005;Suarez-Orozco & Suarez-Orozco, 2001;Zhou, 1997). Reduced school support resulted in decreased educational expectations, consistent with previous research that has found a direct link between school support and student achievement (Woolley, 2007), especially that of immigrant students (Han, 2008). The direct effect of parental absence on decreased educational expectations is also consistent with previous findings (Astone & McLanahan, 1991;Coley, 1998;Hernandez, 2004;Lamb, 1999;SuarezOrozco et al, 2009).…”
Section: How Do Various Experiences Of Parental Absence Affect Academsupporting
confidence: 77%
“…These include gender of the student (Crul & Vermeulen, 2003;Portes & Rumbaut, 2001;Suarez-Orozco & Qin-Hilliard, 2004;Suarez-Orozco & Carhill, 2008;Suarez-Orozco et al, 2009;Way, 2004), difficulties with the English language (Genesee & Gandara, 1999;Hernandez, 2004;Suarez-Orozco & Carhill;Suarez-Orozco et al, 2009), a problematic school environment (Gaytan et al, 2007;Han, 2008;Suarez-Orozco & Carhill;Woolley, 2007), economic hardship (Garibaldi, 1997;Roscigno, 2000;Suarez-Orozco & Carhill;Suarez-Orozco et al, 2010), and reduced parental involvement in the educational process (Barnard, 2004;Hernandez;Gaytan et al;Kuperminc, Darnell, & Alvarez-Jimenez, 2007;Martinez, DeGarmo, & Eddy, 2004;Suarez-Orozco et al, 2010), as well as coming from a single-parent home (Amato & Sobolewski, 2001;Coley, 1998;Lamb, 1999;Suarez-Orozco et al, 2009;Suarez-Orozco et al, 2010).…”
Section: Academic Achievement Among Spanish-speaking Immigrant Studentsmentioning
confidence: 99%
See 1 more Smart Citation